Emergence of Superconductivity in LaOFeAs: Electronic Structure and Lattice Dynamics (Journal of Scientific Research, 2010)
In view of continuing interest in the parent compound of the recently discovered superconducting iron-oxypnictide (LaO1-xFxFeAs) we present fresh results and analyses of ab-initio calculations of the electronic band structure, lattice dynamical properties, and elastic constants assuming it to be insulating as well as metallic. The total and partial electronic density of states (EDOS) of the undoped LaOFeAs in both states are extracted from the electronic band structure. The phonon dispersion and the phonon density of states (PDOS) are also studied. Possible implications of the band structure, EDOS, and PDOS of LaOFeAs on the eventual appearance of high-Tc superconductivity upon carrier doping are discussed. Our findings reveal that phonons are unlikely to mediate Cooper pairing in RE-OFeAs. In addition, the values of various independent elastic constants of the compound assuming both insulating and metallic states are estimated and discussed. Keywords: LaOFeAs; Electronic band structure; Phonon spectrum; Elastic constants; Superconductor.© 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi:10.3329/jsr.v3i1.6211                J. Sci. Res. 3 (1), 1-11 (2011)